2015
DOI: 10.1371/journal.pone.0119396
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-21 Regulates PI3K/Akt/mTOR Signaling by Targeting TGFβI during Skeletal Muscle Development in Pigs

Abstract: MicroRNAs (miRNAs), which are short (22–24 base pairs), non-coding RNAs, play critical roles in myogenesis. Using Solexa deep sequencing, we detected the expression levels of 229 and 209 miRNAs in swine skeletal muscle at 90 days post-coitus (E90) and 100 days postnatal (D100), respectively. A total of 138 miRNAs were up-regulated on E90, and 31 were up-regulated on D100. Of these, 9 miRNAs were selected for the validation of the small RNA libraries by quantitative RT-PCR (RT-qPCR). We found that miRNA-21 was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 49 publications
0
53
0
Order By: Relevance
“…52,53 Moreover, miR-21 targets TGF-b to regulate porcine skeletal muscle development through PI3K/Akt/mTOR signaling. 54 MiR-133 in myogenesis also functions through targeting insulin-like growth factor-1 receptor (IGF-1R) to down-regulate phosphorylation of Akt. 55 Given the fact that PI3K/Akt/mTOR pathway promotes myoblast differentiation and P55PIK is a participant of this pathway, we reason that during terminal differentiation, miR-432 may still use P55PIK as a target gene and exert inhibitory effects on myoblast differentiation through this pathway.…”
Section: ) (H and I) The Results Of Dual Luciferase Reporter Assaymentioning
confidence: 99%
“…52,53 Moreover, miR-21 targets TGF-b to regulate porcine skeletal muscle development through PI3K/Akt/mTOR signaling. 54 MiR-133 in myogenesis also functions through targeting insulin-like growth factor-1 receptor (IGF-1R) to down-regulate phosphorylation of Akt. 55 Given the fact that PI3K/Akt/mTOR pathway promotes myoblast differentiation and P55PIK is a participant of this pathway, we reason that during terminal differentiation, miR-432 may still use P55PIK as a target gene and exert inhibitory effects on myoblast differentiation through this pathway.…”
Section: ) (H and I) The Results Of Dual Luciferase Reporter Assaymentioning
confidence: 99%
“…Additionally, miR-21 has been shown to increase AKT/ mTORC1 signaling by inhibiting Treg differentiation [48,49]. MiR-21 has also been shown to regulate PI3K/AKT/mTOR signaling by targeting TGFβI gene expression [50]. Thus, miR-21 may also regulate Treg cell function through the regulation of the TGF-β/AKT/mTORC1 signaling pathway.…”
Section: Expression Levels Of Mir-21 Foxp3 Tgf-β1 and Smad7 In Pbmcmentioning
confidence: 99%
“…Skeletal-muscle-specific miRNAs, including miR-1, miR-133, miR-206 and miR-208b/499 (Chen et al, 2006;Kim et al, 2006;McCarthy et al, 2009;Yang et al, 2015), muscleenriched miRNAs including miR-486 , and ubiquitous miRNAs including miR-21 (Bai et al, 2015) have all been shown to play important roles in myogenesis.…”
Section: Introductionmentioning
confidence: 99%